2019
DOI: 10.3390/jcm8050743
|View full text |Cite
|
Sign up to set email alerts
|

Expression of PD-1 and CTLA-4 Are Negative Prognostic Markers in Renal Cell Carcinoma

Abstract: Immuno-oncological therapy with checkpoint inhibition (CI) has become a new standard treatment in metastatic renal cell carcinoma (RCC), but the prognostic value of the expression of CI therapy target molecules is still controversial. 342 unselected consecutive RCC tumor samples were analyzed regarding their PD-1, PD-L1, and CTLA-4 expression by immunohistochemistry (IHC). The prognostic values for cancer-specific survival (CSS) and overall survival (OS) were analyzed for those not exposed to CI therapy. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…6 PD-L1 expression by tumor cells is associated with worse prognosis for patients with many types of tumors including ccRCC. 7,8 Although PD-L1 staining appears to correlate with a better outcome from immune-based combinations like nivolumab-ipilimumab, 3 it is a poor discriminating factor for clinical decisions. Furthermore, the evaluation of PD-L1 expression by immunohistochemistry (IHC) has not been yet considered as a gold-standard.…”
Section: Introductionmentioning
confidence: 99%
“…6 PD-L1 expression by tumor cells is associated with worse prognosis for patients with many types of tumors including ccRCC. 7,8 Although PD-L1 staining appears to correlate with a better outcome from immune-based combinations like nivolumab-ipilimumab, 3 it is a poor discriminating factor for clinical decisions. Furthermore, the evaluation of PD-L1 expression by immunohistochemistry (IHC) has not been yet considered as a gold-standard.…”
Section: Introductionmentioning
confidence: 99%
“…In the setting of mRCC, the negative prognostic role of the expression of PD-L1 on tumor cells has been reported in several studies (25,26). Renal cancers showing the expression of PD-L1 on tumor cells display a higher tumor stage, a worse response to TKI therapy and a poorer prognosis (27). In details, in two post hoc analyses of the COMPARZ study and the METEOR and CABOSUN trials, respectively, PD-L1 expression on tumor cells was associated with shorter survival in mRCC patients, irrespectively of the type of targeted therapy received (28,29).…”
Section: Biomarkers Pd-l1mentioning
confidence: 98%
“…Several studies have demonstrated the negative prognostic role of the expression of PD-L1 in the setting of mRCC (70)(71)(72). The expression of PD-L1 on tumor cells was associated with a higher tumor stage and a worse response to TKI therapy in two post-hoc analyses of the COMPARZ study and the METEOR and CABOSUN trials (28,(72)(73)(74). In addition, a meta-analysis including more than 1,300 patients showed that higher PD-L1 expression correlated with an approximately doubling risk of death (75).…”
Section: Possible Future Predictive and Prognostic Biomarkers Pd-l1 Expressionmentioning
confidence: 99%